Numerical and experimental study on deformation of 3D-printed polymeric functionally graded plates: 3D-Digital Image Correlation approach. (1st March 2019) - Amirpour, Maedeh; Bickerton, Simon; Calius, Emilio; Das, Raj; Mace, Brian
Abstract: This paper presents a novel experimental and simulation investigation of quasi-static transverse deformation of 3D printed polymeric Functionally Graded (FG) plates, which obey the distribution of material properties through the length. Graded solid elements with continuous property distribution at different Gauss points were implemented by a user material subroutine (UMAT) in ABAQUS Finite Element (FE) software. In order to validate the proposed graded FE solutions, the original experimental deflection measurements using 3D-Digital Image Correlation (DIC) technique performed to capture transverse deformation of designed and manufactured 3D printed polymeric FG plates. DIC technique involved tracking the motion of geometric features on a specimen surface over the course of an experiment to generate the displacement field experimentally. It was found that the deviation between FE and experimental out of plane deflection for nonlinear FG plates is higher than that of linear FG plates, which is potentially due to the high gradient distribution of the material inclusions. It can be concluded that the presented 3D-digtal image correlation technique provides for transverse deformation of polymeric FG plates. The deflection contours for the FG plate are not symmetric, differences being more prominent for the linear high stiffness ratio combination. The outcomes of this study can be applied to determine the optimum material distribution to produce a controlled-stiffness polymeric FG plate corresponding to prescribed structural characteristics.